Evaluation of Camellia Cultivars and Selections for Growth, Cold-hardiness, Flowering, and Disease Resistance in Tennessee, USA - Madhav Parajuli; Jacob Shreckhise; Donna Fare; Benjamin Moore; Prabha Liyanapathiranage; Pratima Subedi; Fulya Baysal-Gurel (HortScience, 2023)
Susceptibility to low-temperature injury and diseases is a major concern associated with ornamental camellia production. To comprehensively understand their growth, cold-hardiness, flowering, and disease resistance, 24 camellia (Camellia spp. and hybrids) cultivars and selections were evaluated in McMinnville, TN, USA (USDA plant hardiness zone 7a). During Mar 2011, camellias were planted in the field plots. Plant height and canopy width were measured annually from 2011 to 2019, and low-temperature damage was recorded in 2014 and 2023. The flowering duration was recorded each year from 2011 to 2020. The Camellia Yellow Mottle Virus, monochaetia leaf spot (Monochaetia sp.), edema, flower blight (Ciborinia camelliae), and flower spot (Botrytis cinerea) severity (% affected) were evaluated from Oct to Nov in 2016 and 2017. The season-long area under the disease progress curve (AUDPC) was calculated. Cultivars Arctic Snow and Pink Icicle exhibited the greatest height, and Autumn Spirit, Elaine Lee, Arctic Snow, and Survivor had the widest canopy width, whereas Shishigashira had the lowest height and canopy width. ‘April Remembered’, ‘April Rose’, ‘Arctic Snow’, ‘Ashton’s Ballet’, ‘Autumn Carnival’, ‘Autumn Spirit’, ‘Elaine Lee’, ‘Survivor’, and C. chekiangoleosa selection were least affected by winter low temperatures, whereas ‘Korean Snow’, ‘One Alone’, C. sasanqua selection, ‘Pink Icicle’, and ‘Shishigashira’ were severely damaged. ‘Arctic Snow’ flowered most reliably (6 of 8 years), whereas ‘April Remembered’, ‘April Rose’, ‘Ashton’s Ballet’, ‘Autumn Spirit’, and ‘Survivor’ flowered five times. ‘Korean Fire’, ‘Classic Pink’, ‘Maroon Mist’, and ‘Spring’s Promise’ displayed the highest virus severity and AUDPC. ‘Arctic Snow’, C. sasanqua selection, and the C. chekiangoleosa selection had no viral symptoms. C. sasanqua selection and ‘Red Aurora’ were significantly impacted by edema disorder, with severity ratings of ∼43% and 26%, respectively. Monochaetia leaf spot severity was highest in ‘Red Aurora’ and ‘Spring’s Promise’, whereas ‘Anacostia’, ‘Arctic Snow’, ‘Ashton’s Ballet’, ‘Autumn Spirit’, ‘Classic Pink’, ‘Kuro Delight’, ‘One Alone’, ‘Pink Icicle’, ‘Shishigashira’, and ‘Survivor’ exhibited the least monochaetia leaf spot severity and AUDPC. Flower blight and flower spot were observed only in ‘Arctic Snow’ and ‘Survivor’. These findings will aid landscapers and nursery growers with selecting and managing camellia cultivars effectively.